Investigation Of Oxidation Process On SOI Wafer - Salleh, Shaharatul A’ini (Universiti Sains Malaysia, 2022)
Silicon-on-Insulator, SOI wafer technology is widely used in microelectronic devices due to its advantages that have been used to minimize or eliminate substrate leakage and improve design performance. They have fast speeds, error reduction, low power consumption, increased scaling, and latch-up immunity. The purpose of this project is to investigate and study the degree of thickness of the oxide layer formed on SOI wafers after undergoing an oxidation process at various oxidation temperature and time and its influence on the electrical properties of the wafer. Firstly, wafer was cut by 1cm x 1cm size and cleaned by using RCA Cleaning to remove the organic residues ionic and heavy metal atomic contamination. In this study, SOI wafers undergo oxidation process at temperature from 850 ℃ to 1000 ℃ and soaking time from 1 hour to 7 hours at the oxygen gas flow fixed to 200 cc/min. After the oxidation process, the oxide thickness growth on the SOI wafer were be analyzed by using FilMetric measurement. It was found that oxide thickness increased as the oxidation temperature and time increased. By using four-point probe, the resistivity of the SOI wafer was measure and it shows that as the oxidation temperature and time was increased, the resistivity of the wafer sample is decreased. AFM were used to analyzed the effect of wafer surface roughness and wafer topography after the oxidation process. From the AFM results, it can be concluded that when the oxidation temperature and time were increased, the surface roughness of the wafer sample was increased.